Tecnologia Social: an introduction to research, practice and another future - Pozzebon, Marlei; Souza, Ana Clara; Prado Saldanha, Fabio; Bagattolli, Carolina (Organizações & Sociedade, 2025)
Decolonizing our minds and bodies is a slow and arduous process. The Western paradigm, centered on Europe and North America, continues to present itself as universal and superior, relegating the rest of the world to a subordinate and peripheral position. In response, universities and social movements from the Global South have sought to decolonize knowledge production by valuing alternative forms of knowing that have often been rendered invisible. In this context, the concept of tecnologia social emerges as both a theoretical and practical lens, rooted in local cultural traditions and solidarity economy movements. It proposes initiatives that have played a fundamental role in addressing economic and social crises, particularly among vulnerable populations. Although contested, the concept of tecnologia social refers not only to physical artifacts but also to methodologies and ways of organizing. Still relatively unknown within Latin American academia and almost invisible internationally, this approach deserves greater recognition. This thematic call aims to strengthen the field by bringing together critical, theoretical, and practice-based articles committed to tecnologia social and social transformation.